An analysis of SMEs’ attitudes and practices toward tax compliance in Zimbabwe - Nyamwanza, Tonderai; Mavhiki, Severino; Mapetere, Denver; Nyamwanza, Lilian (Midlands State University, 2015)
The informal sector has become the major employer in Zimbabwe, but the sector is not contributing meaningfully to the treasury due to noncompliance on tax remittances by the operators. The research was done on 50 businesses in the retail sector in Gweru. The findings are that minimal efforts are being put in place to enforce compliance, and corruption levels are high among the tax collection officials. Small and medium enterprises (SMEs) evade compliance by paying bribes, keeping two sets of records, relocating to new premises without notifying authorities, and temporarily closing businesses during compliance blitz. Penalties have been found to be the most effective in enforcing compliance. Publicity should be increased by authorities using radio, television, and pamphlets, which were found to be most effective. In addition, the Zimbabwe Revenue Authority (ZIMRA) should give business people more formal tax education to enhance understanding of tax obligations and compliance.